Borysa Popławskiego Uwagi o poezji: autorskie credo a wyobraźnia tłumacza - Ojcewicz, Grzegorz (Acta Polono-Ruthenica, 2018)
This article scrutinizes the structure and content of Boris Poplavsky’s Notes on Poetry. The text reveals the thoughts of this Russian poet who writes about the Russian poetic tradition (Pushkin, Blok) and mentions selected aspects of emigrant reality. B. Poplavsky stresses the importance of an innovative element in the creative process. He indicates the basic mechanisms governing the inner literary process which determine the evolution of fiction.